A Sociological Perspective on Youth, Social Capital and Volunteering: The Case of Izmir Youth Centers - Bayram, Elif N.; Güllüpınar, Fuat (Journal of Applied And Theoretical Social Sciences, 2023)
This research focuses on how young people experience volunteering in public youth centers and how they make sense of volunteering in their own lives, depending on their youth identity, within a historical, factual, and conceptual framework. In this direction, which profiles of youth are the ones engaged in volunteering and in what ways, with which motivations they reach the volunteering activities, and which material and moral benefits they receive in their lives by doing volunteering activities are studied through social capital theory. In the research, semi-structured interviews were conducted with 16 young people between the ages of 17-30 who participated in volunteering activities at the Alsancak Havagazı Youth Center affiliated with the local government in İzmir. Participant observation was conducted for five months in the research, and active participation was developed through different roles in the activities. Böhnisch's concept of "coping with life" aimed to examine how young people's experience of volunteering provided them comfort. The research showed that young people who could participate more often, depending on their living conditions, can derive more meaningful benefits from the relevant activities in the youth center and that the volunteering activities carried out in the youth center allow for differentiation of young people as "project producers" and "project beneficiaries." This situation is explained by Bourdieu's concept of "reproduction."